The Adaptive Challenges of Leadership in Maine Schools - Ackerman, Richard; Mette, Ian; Biddle, Catharine (Maine Policy Review, 2018)
The current landscape of educational leadership in Maine schools offers a range of challenges and uncertainties that are seldom acknowledged or appreciated. These challenges can expose significant gaps between clinical, research-based knowledge and leadership practices in schools in Maine and across the United States. These endemic issues comprise what Heifetz (1994) calls “adaptive challenges.” Solutions to the leadership challenges raised by these issues don’t come quickly or easily and are in fact inherently confusing because they don’t have easy technical answers. In the context of schools, they include responses to the endemic challenges of poverty as it affects families and children in Maine, as well as the nature of instructional leadership to provide better supervision and evaluation of teachers. These issues also inform the principles and practices which guide the development of school leaders in Maine through the educational leadership program at the University of Maine College of Education and Human Development.